APLIKASI SISTEM IRIGASI TETES OTOMATIS UNTUK OPTIMASI LAHAN KERING DI MUSIM KEMARAU DENGAN BUDIDAYA HORTIKULTURA SEMUSIM PADA KELOMPOK TANI FENUN, KECAMATAN TAEBENU, KABUPATEN KUPANG - Muhammad S. Mahmuddin; I G. B. Adwita Arsa; Ari Bangkit Sanjaya Umbu; Yosua Tanggela (Universitas Mataram, 2025)
One of the problems faced by the Fenun Farmers Group. Baumata Village, Taebenu District. Kupang Regency in developing dry land farming is the very limited amount of water in the dry season, so that land productivity decreases and farmers experience difficulties in cultivating horticultural crops. To optimize the productivity of the land, the solution taken is to cultivate seasonal horticultural crops by utilizing automatic drip irrigation technology. Objectives (1) Adopting drip irrigation technology, either manually or automatically, which can be done by farmers. (2) Providing knowledge to farmers about making organic fertilizer from household waste/agricultural waste through direct practice. Methods of implementing activities: (1). Counseling on the importance of drip irrigation in the dry season (2.) Counseling and Practice of drip irrigation equipment installation technology (3) Practice of making solid organic fertilizer (POP) and Liquid Organic Fertilizer (POC) (4) Counseling on the introduction of pests and pathogens. The results of this activity are with the presence in the community service program that has been carried out, farmers are very enthusiastic where there is a discussion about how to cultivate seasonal horticulture with the application of appropriate and effective drip irrigation technology to support water limitations in dry land. The material presented on seasonal horticulture cultivation and the application of manual and automatic drip irrigation technology in dry land was very enthusiastically responded to by the participants of the community partnership program. Based on the activities of this Community Partnership Program, several things were concluded, namely: 1) Members of the Fenun Farmer Group are very enthusiastic about the Community Partnership Program activities carried out both in the form of lectures, discussions, learning together and practicing together, and are interested in implementing a drip irrigation system, 2) Through this activity, the use of drip irrigation can be one solution on agricultural land, especially in Kupang Regency which is an area with low rainfall.